PEMBELAJARAN BERDIFERENSIASI PADA MATEMATIKA KELAS V DI SD NEGERI MENUR MRANGGEN - Rizky Muhammad Abdul Aziz; Joko Sulianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the challenges faced by elementary school students in learning Mathematics, particularly in understanding story problems related to plane geometry. Conventional teaching methods that apply the same approach to all students often fail to accommodate differences in learning readiness, interests, and learning styles. Therefore, differentiated learning was implemented as an alternative approach to create a more inclusive and student-centered learning process. The purpose of this study was to describe the planning, implementation, and evaluation of differentiated learning in Mathematics for fifth-grade students at SD Negeri Menur Mranggen. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, questionnaires, tests, and documentation. The data analysis process involved data reduction, data presentation, and conclusion drawing. The findings revealed that teachers had designed differentiated lesson plans by considering students’ readiness, interests, and learning styles. During the implementation stage, teachers applied flexible grouping strategies, varied learning activities, and adaptive assignments according to students’ characteristics. The evaluation process was carried out continuously through written tests, observation, rubrics, interviews, and personal feedback. The results indicated that differentiated learning increased students’ motivation, participation, confidence, and understanding of mathematical concepts, especially in plane geometry material. In conclusion, differentiated learning proved effective in improving the quality of Mathematics learning in fifth grade at SD Negeri Menur Mranggen, despite limitations in time and supporting facilities.